Colony Growth, Sporulation, and Viability of Entomopathogenic Fungus Beauveria bassiana (Balsamo) Vuillemin on Various Agricultural Waste as Growing Media - Kurniawan, Irvan; Afandhi, Aminudin; Tarno, Hagus (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2022)
Beauveria bassiana is an entomopathogenic fungus that is widely produced for the benefit of biological control agents of various insect pests. The current production that is expected is to use cheap media but produce quality isolates. This study aims to determine colony growth, sporulation and viability of Beauveria bassiana conidia in several agricultural waste media. The experiment was compiled in a complete randomized design and replicated four times. B. bassiana in rice bran media added with cricket flour had the fastest colony growth while B. bassiana in rice husk media was the lowest, lower than the control treatment. In wheat bran media added cricket flour has slower colony growth than rice bran with cricket flour media similar to control treatment but has the second highest sporulation after rice bran with cricket flour media. The highest viability belongs to B. bassiana which is grown on rice bran with cricket flour media. The production in each treatment medium has a real effect but the addition of cricket flour has a significant influence in the production of quality isolates.